2002
DOI: 10.1104/pp.010546
|View full text |Cite
|
Sign up to set email alerts
|

Auxin and Ethylene Response Interactions during Arabidopsis Root Hair Development Dissected by Auxin Influx Modulators

Abstract: The plant hormones auxin and ethylene have been shown to play important roles during root hair development. However, cross talk between auxin and ethylene makes it difficult to understand the independent role of either hormone. To dissect their respective roles, we examined the effects of two compounds, chromosaponin I (CSI) and 1-naphthoxyacetic acid (1-NOA), on the root hair developmental process in wild-type Arabidopsis, ethylene-insensitive mutant ein2-1, and auxin influx mutants aux1-7, aux1-22, and doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
164
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(176 citation statements)
references
References 40 publications
9
164
1
2
Order By: Relevance
“…It has been shown that growth in the presence of either auxin or auxin transport inhibitors results in enhanced root hair length [21,22]. Here we report that exogenous IAA stimulated RH elongation in wt and atpgp4 seedlings (Fig.…”
Section: Root Hairs Of Atpgp4 Mutants Are Longer and More Variablementioning
confidence: 59%
See 3 more Smart Citations
“…It has been shown that growth in the presence of either auxin or auxin transport inhibitors results in enhanced root hair length [21,22]. Here we report that exogenous IAA stimulated RH elongation in wt and atpgp4 seedlings (Fig.…”
Section: Root Hairs Of Atpgp4 Mutants Are Longer and More Variablementioning
confidence: 59%
“…in length Like for LRs, RH initiation and elongation is well known to be regulated by auxin [22]. The growth defect of LRs in the atpgp4 mutants thus prompted us to investigate RH number and lengths in atpgp4.…”
Section: Root Hairs Of Atpgp4 Mutants Are Longer and More Variablementioning
confidence: 99%
See 2 more Smart Citations
“…27 In addition, this study provides evidence that HOS1 also plays a role in ethylene regulation of leaf expansion. Given that auxin and ethylene signaling is elaborately intertwined, [32][33][34] HOS1 might establish an important crosstalk. Auxin biosynthesis and ethylene signaling would be coordinated to fine-tune HOS1-mediated developmental processes.…”
mentioning
confidence: 99%